An Oligopolistic Model of a Japanese Pharmaceutical Company - Hiroki Tsurumi; Yoshi Tsurumi (Queen's University, Department of Economics, 1970)
Earlier the first author built an oligopolistic model of the American automobile firms, demonstrating the possibility of econometric model building at the firm level. In the present paper, on the basis of detailed corporate data, we advance this effort further using a more elaborate behavioral hypothesis concerning the behaviors of a firm under oligopolistic situation. Furthermore, we will experiment with elaborate estimation procedures.
Keywords: 330